Comparative analysis of state and civil society discourse on the implementation of the United Nations' convention on the rights of the child in North Africa. Issue 1 (1st January 2017) - Chaney, Paul
ABSTRACT: In the face of continuing children's rights abuses across North Africa, the need for governments to engage non-state actors in human rights implementation is explicit in the United Nations' convention on the rights of the child (UNCRC). Hitherto, this has largely escaped scholarly attention. It is a lacuna addressed in this paper, which presents a theoretically informed analysis of the role of civil society as a political space for promoting children's rights in six countries with particular reference to Egyptian and Sudanese policy and practice. Critical discourse analysis of state and civil society submissions to the second-cycle United Nations' Universal Periodic Review provides insight into UNCRC implementation. The findings show key contrasts in the salience and framing of a range of issues including: violence against children, education, health, forced marriage and discrimination. The wider significance of this is manifold: it offers an original transferable methodology, highlights the formative role of discourse and underlines a pronounced asymmetry in the power of government and civil society. Furthermore, the Egyptian and Sudanese case studies reveal key implementation pathologies applying to authoritarian and (post-)conflict states.